ARABIC-IMAM BADR AL-DIN AL-AYNI AND HIS LEVEL IN ISLAMIC JURISPRUDENCE - Omar Kera (دی اسکالر)
This article is about Imam Al-Ayni and the jurisprudential status he attained. Therefore, it was necessary to provide a biography of him, identifying his upbringing and mentors, from when he was a young child until he became a scholar of great stature and standing. We also need to learn about the students he left behind, and the books he authored and left behind as a treasure for Muslims to draw from in them of various sciences, from jurisprudence, language, hadith, and others. Then, to understand Al-Ayni's jurisprudential standing and his class among scholars, it was necessary to address what previous scholars have said about the classes of jurists and explain the conditions for each class. After discussing the classes of jurists and the conditions that must be met by those in each class, we moved on to discuss Imam Al-Ayni's standing, conveying the words of the scholars of his time and those who came after him about him. We also examined his books and how scholars received them after him, how much they quoted from him, and whether they accepted his opinions and statements or not. We found that he authenticated and preferred some jurisprudential sayings over others. A number of scholars who came after him corrected and preferred it. Through all of this, we were able to accurately determine his class. Then we followed that by mentioning some of the issues in which Al-Ayni preferred one opinion of the scholars over another.